North American Wildland Plants, Third Edition : A Field Guide - Stubbendieck, James L.; Hatch, Stephan L., 1945-; Bryan, Neal M.; Dunn, Cheryl D. (Book collections on Project MUSE., 2017)
"North American Wildland Plants contains descriptions of the salient characteristics of the most important wildland plants of North America. This comprehensive reference assists individuals with limited botanical knowledge as well as natural resource professionals in identifying wildland plants. The two hundred species of wildland plants in this book were selected because of their abundance, desirability, or poisonous properties. Each illustration has been enhanced with labels pointing to key characteristics to facilitate the identification of unknown plants. Each plant description includes plant characteristics, an illustration of the plant with enlarged parts, and a general distribution map for North America. Each species description includes nomenclature; life span; origin; season of growth; inflorescence, flower or spikelet, or other reproductive parts; vegetative parts; and growth characteristics. Brief notes are included on habitat; livestock losses; and historic, food, and medicinal uses. This third edition contains additional refinements in the nomenclature, distribution, illustrations, and descriptions of plants."